The centrality of RNA for engineering gene expression. Issue 12 (4th October 2013) - Chappell, James; Takahashi, Melissa K.; Meyer, Sarai; Loughrey, David; Watters, Kyle E.; Lucks, Julius
Abstract Synthetic biology holds promise as both a framework for rationally engineering biological systems and a way to revolutionize how we fundamentally understand them. Essential to realizing this promise is the development of strategies and tools to reliably and predictably control and characterize sophisticated patterns of gene expression. Here we review the role that RNA can play towards this goal and make a case for why this versatile, designable, and increasingly characterizable molecule is one of the most powerful substrates for engineering gene expression at our disposal. We discuss current natural and synthetic RNA regulators of gene expression acting at key points of control – transcription, mRNA degradation, and translation. We also consider RNA structural probing and computational RNA structure predication tools as a way to study RNA structure and ultimately function. Finally, we discuss how next‐generation sequencing methods are being applied to the study of RNA and to the characterization of RNA's many properties throughout the cell.